Nanoplasmonics, Nano-Optics, Nanocomposites, and Surface Studies Selected Proceedings of the Second FP7 Conference and the Third International Summer School Nanotechnology: From Fundamental Research to Innovations, August 23-30, 2014, Yaremche-Lviv, Ukraine - Fesenko, Olena; Yatsenko, Leonid (Springer Proceedings in Physics, 2015)
This book highlights the most recent advances in nanoscience from leading researchers in Ukraine, Europe, and beyond.  It features contributions from participants of the 3rd International Summer School "Nanotechnology: From Fundamental Research to Innovations," held in Yaremche, Ukraine on August 23-26, 2014 and of the 2nd International NANO-2014 Conference, held in Lviv, Ukraine on August 27-30, 2014.  These events took place within the framework of the European Commission FP7 project Nanotwinning, and were organized jointly by the Institute of Physics of the National Academy of Sciences of Ukraine, University of Tartu (Estonia), University of Turin (Italy), and Pierre and Marie Curie University (France).  Internationally recognized experts from a wide range of universities and research institutions share their knowledge and key results in the areas of nanocomposites and nanomaterials, nanostructured surfaces, microscopy of nano-objects, nano-optics and nanophotonics, nanoplasmonics, nanochemistry, nanobiotechnology, and surface enhanced spectroscopy.  • Covers nanocomposites, nanostructured surfaces, and nanobiotechnology • Presents state-of-the-art advances in nanoplasmonics, nanomaterials characterization, and surface enhanced spectroscopy • Represents essential reading for advanced undergraduate and graduate students through practicing university and industry researchers.